PENGARUH PERHATIAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA KELAS XI SMA NEGERI 5 PEKANBARU - Eva Arni Salisah; Gimin Gimin; Zahirman Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is motivated by problems that arise from observations made by researchers, namely the lack of motivation of students in learning. This can be seen from the fact that there are students who lack enthusiasm in participating in learning activities, students often do not do homework (PR), when given assignments some students are more likely to wait for their friends’ assignments that have been completed, and imitate their friends’assignments. This is due to lack of parental attention. The formulation of the problem in this study is how the influence of parents’ attention to the motivation of students of class XI SMA Negeri 5 Pekanbaru. The purpose of this study was to determine the effect of parental attention on the learning motivation of students of class XI SMA Negeri Pekanbaru. This research method is quantitative descriptive. The population in this study were all students of class XI SMA Negeri 5 Pekanbaru with a total of 438 students. The sample in this study were 66 students with proportional random sampling technique. Data collection techniques are observation, questionnaire, documentation and literature. Data collection instruments used in this study were questionnaires consisting of 18 statements about student learning motivation. Data analysis techniques using simple linear regression and processed using SPSS version 16. The results showed that the learning motivation of class XI SMA Negeri 5 Pekanbaru was categorized as “high” (55,65%). Whereas the attention of parents is categorized as “adequate” (67,87). It is known that a simple linear regression analysis is obtained Fhitung ≥ Ftabel or 75,129 ≥ 3,99 and simple linear regression equation that is Y=18,2590,825X then H0 rejected. This means that there is an influence of parents’ attention to of class XI SMA Negeri 5 Pekanbaru.Keywords: Student Learning Motivation, Influence Of Parental Attention